Three Book Reviews - Kent Parades Scribner; Susan Haag; Steven J. Fountaine (Arizona State University, 1993)
This issue of the Archives contains reviews of three books: Robert Leestma and Herbert J. Walberg (Eds.), Japanese Educational Productivity, reviewed by Steven J. Fountaine, Thomas Sowell, Inside American Education: The Decline, the Deception, the Dogmas, reviewed by Susan Haag, Chester E. Finn Jr. and Theodor Rebarbar (Eds.), Education Reform in the '90s, reviewed by Kent Parades Scribner